2019
DOI: 10.1038/s41598-018-37827-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Aspergillus niger NBC001 underlying suppression against Heterodera glycines

Abstract: Heterodera glycines is the most pervasive soybean pests worldwide. Biocontrol provides a strategy to sustainably control nematodes. In this study, 22 fungal isolates were obtained and identified from cysts of Heterodera spp. Among them, Aspergillus niger NBC001 showed high nematicidal activity against H. glycines. The 2-fold dilution of NBC001 culture filtrate caused 89% mortality of second-stage juveniles and inhibited more than 98% of egg hatching in vitro. In both pot and field experiments, the numbers of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Aspergillus spp. are very common in soil and are lethal to the nematode population; A. niger and A. candidus were the potential fungal agents to be used against plant-parasitic nematodes [35,42,43]. The results of this study indicated that fermentation of the A. japonicus ZW1 from soil was found to not only inhibit egg hatching but was also toxic to nematodes in vitro.…”
Section: Discussionmentioning
confidence: 82%
“…Aspergillus spp. are very common in soil and are lethal to the nematode population; A. niger and A. candidus were the potential fungal agents to be used against plant-parasitic nematodes [35,42,43]. The results of this study indicated that fermentation of the A. japonicus ZW1 from soil was found to not only inhibit egg hatching but was also toxic to nematodes in vitro.…”
Section: Discussionmentioning
confidence: 82%
“…Crop plants encounter different abiotic stress challenges—including excessive temperature, drought, salinity, floods, and heavy metal accumulation—which exclusively affect crop plant growth and yield [ 201 , 202 ]. Most cultivated lands face one or more of the above-listed stresses, which decrease crop plants’ yields by up to 70% [ 203 ].…”
Section: Beneficial Aspects Of Rhizosphere-resident Pgpfmentioning
confidence: 99%
“…It has been extensively used for controlling white mould in oilseed rape, cabbage, soybean, common bean, and other important cash crops (Steadman, 1979; Jones et al ., 2014; Zhang et al ., 2016; Hu et al ., 2016b; Sabaté et al ., 2018). Mycoparasitic potential of Aspergillus against broad range of plant pathogenic fungi, bacteria and nematodes was previously demonstrated (Israel and Lodha, 2005; Patibanda and Sen, 2005; Adebola and Amadi, 2010; Jang et al ., 2016; El‐Debaiky, 2017; Alshannaq et al ., 2018; Boughalleb‐M'Hamdi et al ., 2018; Jin et al ., 2019). The mechanisms by which Aspergillus can eliminate the opponent fungal pathogens were studied.…”
Section: Introductionmentioning
confidence: 99%